Use of brain diffusion tensor imaging for the prediction of long-term neurological outcomes in patients after cardiac arrest: a multicentre, international, prospective, observational, cohort study. Issue 4 (April 2018) - Velly, Lionel; Perlbarg, Vincent; Boulier, Thomas; Adam, Nicolas; Delphine, Sebastien; Luyt, Charles-Edouard; Battisti, Valentine; Torkomian, Gregory; Arbelot, Charlotte; Chabanne, Russell; Jean, Betty; Di Perri, Carol; et al.
Summary: Background: Prediction of neurological outcome after cardiac arrest is a major challenge. The aim of this study was to assess whether quantitative whole-brain white matter fractional anisotropy (WWM-FA) measured by diffusion tensor imaging between day 7 and day 28 after cardiac arrest can predict long-term neurological outcome. Methods: This prospective, observational, cohort study (part of the MRI-COMA study) was done in 14 centres in France, Italy, and Belgium. We enrolled patients aged 18 years or older who had been unconscious for at least 7 days after cardiac arrest into the derivation cohort. The following year, we recruited the validation cohort on the same basis. We also recruited a minimum of five healthy volunteers at each centre for the normalisation procedure. WWM-FA values were compared with standard criteria for unfavourable outcome, conventional MRI sequences (fluid-attenuated inversion recovery and diffusion-weighted imaging), and proton magnetic resonance spectroscopy. The primary outcome was the best achieved Glasgow-Pittsburgh Cerebral Performance Categories (CPC) at 6 months, dichotomised as favourable (CPC 1–2) and unfavourable outcome (CPC 3–5). Prognostication performance was assessed by the area under the receiver operating characteristic (ROC) curves and compared between groups. This study was registered withClinicalTrials.gov, numberNCT00577954 . Findings: Between Oct 1, 2006, and June 30, 2014, 185 patients were enrolled in the derivation cohort, of whom 150 had an interpretable multimodal MRI and were included in the analysis. 33 (22%) patients had a favourable neurological outcome at 6 months. Prognostic accuracy, as quantified by the area under the ROC curve, was significantly higher with the normalised WWM-FA value (area under the ROC curve 0·95, 95% CI 0·91–0·98) than with the standard criteria for unfavourable outcome or other MRI sequences. In a subsequent validation cohort of 50 patients (enrolled between April 1, 2015, and March 31, 2016), a normalised WWM-FA value lower than 0·91, set from the derivation cohort, had a negative predictive value of 71·4% (95% CI 41·9–91·6) and a positive predictive value of 100% (90·0–100), with 89·7% sensitivity (75·8–97·1) and 100% specificity (69·1–100) for the prediction of unfavourable outcome. Interpretation: In patients who are unconscious 7 days after cardiac arrest, the normalised WWM-FA value, measured by diffusion tensor imaging, could be used to accurately predict neurological outcome at 6 months. This evidence requires confirmation from future large-scale trials with a strict protocol of withdrawal or limitation-of-care decisions and time window for MRI. Funding: French Ministry of Health, French National Agency for Research, Italian Ministry of Health, and Regione Lombardia.